PANCASILA SEBAGAI LANDASAN MORAL DAN ETIKA DALAM KEHIDUPAN BERBANGSA - Perangin-angin, Debi Servinta; Masniar; Frengki Pangaribuan; Sadrah Mesak Manik; Sri Yunita; Surya Dharma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Pancasila as the foundation of the state and the ideology of the Indonesian nation has an important role in shaping the morals and ethics of society in national life, especially in the context of character formation starting from elementary education. This study aims to explore and understand the implementation of Pancasila values ​​in elementary school education and evaluate its impact on the formation of student character. Using a qualitative approach and case study method, this study was conducted in several elementary schools in Biru Biru District. Data were collected through interviews, learning observations, and analysis of curriculum documents. The results of the study showed that the majority of teachers (80%) considered Pancasila education very important in shaping students' character, with 75% stating that values ​​such as honesty, mutual cooperation, and tolerance were important foundations in learning. As many as 70% of teachers applied interactive learning methods, such as group discussions and role plays, which were considered effective in increasing student participation. In addition, the results of observations showed an increase in attitudes of tolerance, social responsibility, and cooperation skills among students. However, the main challenge in teaching Pancasila is the limited availability of relevant and interesting teaching materials. This study emphasizes the importance of Pancasila education in shaping the nation's character and recommends strengthening curriculum support, teacher training, and parental involvement to strengthen the implementation of Pancasila values ​​in national life.